Sistem Informasi Pengelola Berita Acara dan Reservasi Guest House Pada Saung Angklung Udjo - Wim Prismayadi; Daniel Jahja Surjawan (Maranatha University Press, 2016)
In the development of technology, web-based application used to inform the news and events online. It is also experienced by Saung Angklung Udjo, hereinafter referred to SAU. SAU is a Sundanese Arts Studio founded by Udjo Ngalagena as the venue, the center of handicrafts from bamboo, and bamboo musical instrument workshop. People are increasingly interested in Indonesian culture, especially Angklung introduced by SAU, but not everyone can be informed about news and events from SAU with ease. In addition, the SAU also have a Guest House and Venue that is rented out to visitors who attend and want to stay. Currently the rental has not been recorded properly in the process of calculating financial data. Therefore SAU requires a web-based system that can be accessed online, so the owner can control all the activities. The visitors who saw the news and events most in demand will also be stored and analyzed to produce a graph, where the owner can know the visitor traffic over a period time. The purpose of this research is to make Saung Angklung Udjo inform about news and events as well as all related content online, in addition to the convenience of visitors to explore the website is also a concern